Oral health related disorder among children with behavioral problems - Khatun, Mst. Mahmuda; Shahid, Shelina Fatema Binte; Gaffar, Foyjunnesa; Uddin, Md. Nizam (International Journal of Research in Medical Sciences, 2023)
Background: The best mouth function, the absence of disease, and oral health are achieved by maintaining the highest self-esteem possible. When someone has good dental health, they can communicate and connect with people without getting sick, feeling uncomfortable, or feeling embarrassed. This study aimed to evaluate the Oral health-related disorder specifically to assess dental caries and gingivitis among children with behavioral problems. Methods: This study was a prospective cross-sectional investigation carried out at Kalachandpur Government Primary School and Jashim Uddin Institute, Dhaka. The study was carried out between October 2021 and December 2022 and included 650 pediatric patients who were aged between 6 to 15 years. Results: Most 290 (44.62%) children were aged 6-9 years, 250 (38.46%) were 10-12 years, and the rest 110 (16.92%) were 13-15 years old. Patients with 11-15 years had lower dental caries. 310 (48%) were female, and 340 (52%) were male. Dental caries is associated with elevated risk. Children in the elevated caries risk group had a significantly higher mean value of conduct problems and Hyperactivity/inattention based on the SDQ compared to those with low caries risk. No statistically significant differences were found between the low caries risk group and the elevated caries group for the other subscales. Conclusions: There were statistically more children in the study group who had a high risk of getting caries. Behavior problems were observed while externalizing children who had a high risk of getting caries. Children with externalizing behavior also have more conduct problems and hyperactivity compared to children with reduced caries risk.